Teaching Ethnology and Ethnography during Global Pandemic: Few Remarks from Slovakia - Uhrin, Michal (Civilia, 2021)
In the middle of March 2020, due to the global pandemic of Covid-19 disease, Comenius University in Bratislava switched to distance method of education. The transition to distance teaching and learning and restriction of contact with "unknown people" profoundly affected the teaching activities of the Department of Ethnology and Museology, Faculty of Arts, Comenius University in Bratislava. In this paper I describe how the way of teaching theory and methodology of ethnology and socio-cultural anthropology as well as methods and techniques, utilised in ethnographic research, had to be adapted to novel conditions. I will also address how the structure of ethnographic field research, conducted by first year bachelor students of ethnology, had to be changed regarding government restrictions associated with Covid-19 pandemic.
Keywords: Ethnography; Ethnology; Field research; Covid-19; Pandemic; Slovakia